Ecologies of urbanism in India metropolitan civility and sustainability - Rademacher, Anne; Sivaramakrishnan, K. 1957- (UPCC book collections on Project MUSE., 2013)
This book seeks to understand how rapidly proliferating and resource-intensive urbanism affects everyday lived environments and the ecological processes that undergird them in Indian cities. Case studies on nature conservation in the city, urban housing and slum development, waste management, the history and practice of urban planning, and contestations over the quality of air, water, and sanitation in the major cities of Delhi and Mumbai, illuminate the urban ecology perspective at different points across the twentieth century. The book therefore explores how struggles over the environment and quality of life in urban centers are increasingly framed in terms of their future place in a landscape of global sustainability, and the future relationship between cities and their changing hinterlands. It brings both historical particularity and ethnographic nuance to the questions of urban ecology in Indian cities, offering novel insights into some of the most vital theoretical and practical debates on urbanism and sustainability.